The Application of geographic information system (GIS) for shop houses data storage at Jalan Kesuma 3/6 and Jalan Kesuma 3/7, Bandar Tasik Kesuma, Semenyih, Selangor Darul Ehsan / Muhamad Husaini Muhamad Mokhtar - Muhamad Husaini, Muhamad Mokhtar (2020)
Now days , each area must have same problems which is vacant shop houses and don't have a complete data storage about shop houses. Geographic Information System (GIS) is the fast and effective search information is important for systems that involve large data. To address the problem of shop houses data storage which is using geographic information system (GIS) commercial activities management system at shop houses involving dozens or hundreds of shop houses. So without using the GIS it very difficult to find or search the specific information of shop houses and don't have or can't show the data visually. This system focuses on finding the shop houses information using geographical position. The new system also provides mapping and deployment functions, panning, data identification, buffer requests to facilitate the management of manipulating existing data. The use of data disclosure in Geographic Information System (GIS) can help management get faster and more interactive data.